The Transformation of Public Service Law in Smart Cities: Balancing Technological Innovation, Accountability, and Inclusive Governance - Aziz Widhi Nugroho; Dewa Gede Sudika Mangku; Fahrizal S.Siagian (Discourse Journal on Law and Society, 2025)
The rapid development of smart cities, integrating technologies like artificial intelligence (AI), the Internet of Things (IoT), and big data analytics, has transformed urban environments, improving public services and governance. However, this progress presents challenges in inclusivity, accountability, and equity, requiring updates to public service law to address emerging concerns. As digital technologies reshape governance, legal frameworks must balance innovation with citizens' rights protection. This study explores the intersection of law, technology, and society in smart cities, focusing on the implications of digital transformation on public service law. It identifies challenges in governance, including the digital divide, privacy protection, and data security. The research aims to propose an inclusive legal framework that supports technological innovation while promoting accountability and social equity in smart cities. A socio-legal approach is used, combining case studies, policy analysis, and stakeholder interviews. The findings reveal that while digital transformation improves efficiency, challenges remain in citizen participation and reducing inequalities. Successful smart city models, such as those in Barcelona and Tallinn, prioritize inclusivity, accountability, and participation. The study highlights the need for flexible, adaptive legal frameworks to ensure that smart cities are governed inclusively, transparently, and equitably.